2013
DOI: 10.1371/journal.pone.0060456
|View full text |Cite
|
Sign up to set email alerts
|

Is Active Management the Key to the Conservation of Saproxylic Biodiversity? Pollarding Promotes the Formation of Tree Hollows

Abstract: Trees with hollows are key features sustaining biodiversity in wooded landscapes. They host rich assemblages of often highly specialised organisms. Hollow trees, however, have become rare and localised in Europe. Many of the associated biota is thus declining or endangered. The challenge of its conservation, therefore, is to safeguard the presence of hollow trees in sufficient numbers. Populations of numerous species associated with tree hollows and dead wood are often found in habitats that were formed by for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 37 publications
1
51
0
2
Order By: Relevance
“…With regards to oaks, Ranius et al (2009) described a very slow process, with about 200-300 years required for 50% of trees to develop cavities and 400 years are required for all oaks to develop cavities. In a study on Salix alba, Sebek et al (2013) found a probability of cavity formation of approximately 80% in pollards with a diameter of 30-60cm, but only approximately 30% of non-pollards of the same diameter class developed cavities. On the landscape scale, Kirby (2015 suggested a model of regeneration as a series of episodic events, rather than a continuous recruitment of young trees.…”
Section: Conclusion and Implication For The Conservation Of O Eremitamentioning
confidence: 97%
“…With regards to oaks, Ranius et al (2009) described a very slow process, with about 200-300 years required for 50% of trees to develop cavities and 400 years are required for all oaks to develop cavities. In a study on Salix alba, Sebek et al (2013) found a probability of cavity formation of approximately 80% in pollards with a diameter of 30-60cm, but only approximately 30% of non-pollards of the same diameter class developed cavities. On the landscape scale, Kirby (2015 suggested a model of regeneration as a series of episodic events, rather than a continuous recruitment of young trees.…”
Section: Conclusion and Implication For The Conservation Of O Eremitamentioning
confidence: 97%
“…Therefore, forest management of SCIs should aim at maintaining or restoring the typical biological diversity associated with habitat structure and functions, with appropriate management plans (Article 6). How habitat structure and associated saproxylic beetle communities should be maintained or restored is a challenging question (Vodka et al 2008, Sebek et al 2013, with particular e) The conservation status of a natural habitat will be taken as "favourable" when: -its natural range and areas it covers within that range are stable or increasing and -the specific structure and functions which are necessary for its long-term maintenance exist and are likely to continue to exist for the foreseeable future and -the conservation status of its typical species is favourable as defined in (i); i) The conservation status will be taken as "favourable" when: -population dynamics data on the species concerned indicate that it is maintaining itself on a long-term basis as a viable component of its natural habitats and -the natural range of the species is neither being reduced nor is likely to be reduced for the foreseeable future and -there is, and will probably continue to be, a sufficiently large habitat to maintain its populations on a long-term basis; reference to the Mediterranean basin which has high and poorly known levels of diversity and endemism (Baselga 2008). The long lasting association of C. cerdo with old and decaying trees (Buse et al 2007(Buse et al , 2008a suggests that trees colonised by C. cerdo represent keystone structures (Tews et al 2004) to maintain saproxylic diversity and functions associated with Mediterranean protected oak habitats (Sirami et al 2008).…”
Section: Managing Cerambyx Cerdo and Mediterranean Oaks Under The Habmentioning
confidence: 99%
“…Retention forestry is also emerging as a practical way to harvest forest and maintain or restore old-growth features of landscapes (Fedrowitz et al 2014, Mason andZapponi 2015). Management options to protect C. cerdo and related habitat structures and functions range therefore from strict protection of old growth forests, to conservation of habitat trees over managed landscapes, and to forest harvesting coupled with grazing and retention (Sirami et al 2008, Vodka et al 2008, Sebek et al 2013, Fedrowitz et al 2014, Mason and Zapponi 2015. Traditional forest management practices are thus seen as potential conservation tools to protect saproxylic communities (Buse et al 2007, Vodka et al 2008, as well as sustainable and viable production systems (Scarascia-Mugnozza et al 2000, Sjölund andJump 2013).…”
Section: Managing Cerambyx Cerdo and Mediterranean Oaks Under The Habmentioning
confidence: 99%
“…Full development or restoration of coppiced or pollarded stands may require decades to centuries, however. So far, these processes have rarely been investigated beyond pure observations [62].…”
Section: Interventionsmentioning
confidence: 99%